Alice Neel people come first - Neel, Alice 1900-1984; Brown, Meredith; Bryan-Wilson, Julia 1973-; Temkin, Susanna V. (The Metropolitan Museum of Art, 2021)
Alice Neel's (1900-1984) uncompromising artistic vision and deep engagement with humanity in both art and politics have earned her legions of admirers. This beautifully designed and illustrated book surveys the artist's nearly 70-year career, focusing on her long residency in New York, a place that provided her with lifelong inspiration. In addition to her compelling portraits of individuals of all ages, both famous and unknown, Alice Neel: People Come First also considers her remarkable nudes, still lifes, cityscapes, and erotic pastels and watercolors-all considered through the lens of radical humanism that informed so much of the artist's work. Leading scholars delve into various aspects of Neel's practice, revealing that humanism was both a political and philosophical ideal for the artist. The authors address Neel's paintings of LGBTQ subjects; her unique aesthetic language, which merged elements of abstraction and figuration; and her commitment to progressive politics, civil rights, feminism, and racial diversity. The book's essays also explore Neel's highly personal preoccupations with death, illness, and motherhood while reasserting her place in the broader cultural history of the 20th century.00Exhibition: The Metropolitan Museum of Art, New York, USA (15.03.-01.08.2021) / Guggenheim, Bilbao, Spain (17.09.2021-30.01.2022) / de Young Museum, San Francisco, USA (12.03.-09.07.2022)
"This catalogue is published in conjunction with Alice Neel: People Come First, on view at The Metropolitan Museum of Art, New York, from March 15 through August 1, 2021, at the Guggenheim Museum Bilbao from September 17, 2021, through January 30, 2022, and at the de Young Museum, Fine Arts Museums of San Francisco, from March 12 through July 10, 2022." -- Colophon
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Neel, Alice -- 1900-1984; Neel, Alice / 1900-1984 / Exhibitions; Portrait painting, American / 20th century / Exhibitions; Neel, Alice / 1900-1984; Portrait painting, American; 1900-1999; Exhibition catalogs; Ausstellungskatalog -- Metropolitan Museum -- 15.03.2021-01.08.2021 -- New York; Ausstellungskatalog -- Guggenheim Museum -- 17.09.2021-30.01.2022 -- Bilbao; Ausstellungskatalog -- de Young Museum, Fine Arts Museums -- 12.3.2022-10.07.2022 -- San Francisco; Bildband